Work-related factors in the etiology of symptoms of post-traumatic stress among first responders: the Brazilian Firefighters Longitudinal Health Study (FLoHS) - Alina Gomide Vasconcelos; Eduardo de Paula Lima; Kevin Teoh; Elizabeth do Nascimento; Sara MacLennan; Tom Cox (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2021)
Abstract: Two important aspects must be accounted for when discussing the mental health of first responders and, in particular, their report of post-traumatic stress symptoms (PTSS). The first concerns the provision of quantitative data from longitudinal study designs, the second concerns the sophistication of the work-related model used to frame such studies. This is a report on the development of a model for Brazilian firefighters who also work as first responders, from the establishment of a longitudinal panel design study, the Brazilian Firefighter Longitudinal Health Study (FLoHS). The first objective was to compare trainee and active firefighters based on their follow-up data with a nationwide sample of similarly aged Brazilians. The second was to test the effect that operational and organizational experiences had on firefighters' PTSS level during follow up. At baseline, trainee firefighters came from higher socioeconomic backgrounds, were healthier and less exposed to trauma compared to a similarly aged national sample. At follow up, they reported higher prevalence of smoking, sleep problems, anhedonia and were more likely to be overweight. PTSS was predicted by operational and organizational stressors, even when controlled for health status at baseline. The results present not only the differences in the predictive status of operational and organizational events in relation to PTSS, but also how the effects of such events might interact. The data suggest the need for evidence-based interventions, support provided and changes at work environments to improve report rates for mental health in general and for PTSS in particular.